Penyuluhan Tentang Hipertensi Pada Lansia Di Rt 33 Rw 04 Kelurahan Pematang Gubernur - Rika, Rika; Afni, Nurul; Maryani, Tini; Dismawati, Yenni; Destiana, Yeyen; Jumita, Jumita; Rohani, Tuti; Azissah, Danur (LPPM Universitas Dehasen Bengkulu, 2025)
Real Work Lectures (KKN) are a golden bridge for students to transform theoretical knowledge into real action in the context of society. Through direct experience in RT 33 RW 04 Pematang Governor Subdistrict, we identified the high prevalence of hypertension as the main problem. The aim of this research is to analyze the risk factors that contribute to hypertension and develop a simple intervention program that can be implemented by the community. The research method we use is counseling. The results of the research show that outreach increases public knowledge about hypertension.